Strategi Asatidz dan Asatidzah dalam Pembinaan Akhlakul Karimah Santri Di TPQ At-Tadzkir Kecamatan Pemali Kabupaten Bangka - Rizki, M. Thaib; Farikhin, Saiful Farikhin (Edugama: Jurnal Kependidikan dan Sosial Keagamaan, 2022)
The reason the researcher chose this title was to find out the teacher's strategy in fostering the morality of students and Asatidz and Asatidzah's strategies in fostering the morality of students at TPQ At-Tadzkir, Pemali District, Bangka Regency. This research is descriptive qualitative research, which provides a report on research results by describing and explaining the data obtained regarding the Asatidz and Asatidzah strategies in fostering the morality of students at TPQ At-Tadzkir. The research location is at TPQ At-Tadzkir, Pemali District, Bangka Regency, which is located in Air Ruai Village. Sources of data obtained are primary data sources and secondary data sources. The research subjects consisted of 4 Asatidz-Asatidzah, and 16 students (10 male, 6 female). The data collection method in this study used structured interviews, structured observations and documentation. While the data analysis method uses data reduction taken from interview guidelines, observation guidelines, drawing conclusions based on the facts that have been found from the results of the study. Based on the results of the study, it shows the strategy of Asatidz and Asatidzah in fostering the morality of students. First, in the teaching and learning process that takes place at TPQ At-Tadzkir, Pemali District, Bangka Regency, Asatidz and Asatidzah use a teaching event structure including: introverted or closed teaching, namely by using lecture and demonstration methods, while extrovert or open, namely by using the question and answer method and discussion, Second, the roles of Asatidz-Asatidz and santri in processing messages include: expository teaching and heuristic and hypothetical teaching, Third, Asatidz and Asatidz's strategies in processing messages include: deductive processes (from general to specific), and inductive processes (from specific to specific). general), Fourth, learning objectives as teaching strategies at TPQ At-Tadzkir include: intellectual skills, cognitive strategies, verbal information, motor skills, and attitudes of students.